Characterization of polyphenols and carbohydrates exuded by Phaeodactylum tricornutum diatom grown under Cu stress - Milagros Rico; Paula Santiago-Díaz; Argimiro Rivero; Juana Magdalena Santana-Casiano (Scientific Reports, 2024)
Abstract This study is focused on analysing polyphenols and carbohydrates released by Phaeodactylum tricornutum (P. tricornutum) diatoms cultured in natural seawater enriched with sublethal and lethal Cu doses. Cu concentrations of 0.31, 0.79 and 1.57 µM reduced cell densities by 37, 82 and 91%, respectively, compared to the control. The total sum of all identified polyphenols and total carbohydrates released by cells grown under lethal Cu levels increased up to 18.8 and 107.4 times, respectively, compared to data from a control experiment. Four different in vitro assays were used to estimate the antioxidant activities of the extracellular compounds: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical inhibition, cupric ion reducing antioxidant capacity (CUPRAC), ferric reducing antioxidant power and Cu complexing ability (CCA). The highest antioxidant activities were observed in the Cu lethal treatments, where the CCA assay exhibited a greater increase (up to 32.2 times higher than that found in the control experiment) to reduce the concentration of free Cu in the medium and its toxicity. The presence of Cu stimulated the release of polyphenols and carbohydrates to the medium as a detoxification mechanism to survive under lethal levels of Cu regulating its speciation.